POTENSI ANTIBAKTERI EKSTRAK DAUN JARAK PAGAR (Jatropha Curcas L.) TERHADAP STAPHYLOCOCCUS AUREUS DENGAN METODE DILUSI CAIR TERMODIFIKASI DAN DIFUSI AGAR - Sesilia Rante Pakadang; Sisilia Teresia Rosmala Dewi; Tahir Ahmad; Iip Prihartini; Fausiah Razak (Media Farmasi XXX, 2021)
Antibacterial Potential Of Leaf Extract (Jatropha curcas l.) Against Staphylococcus aureus by Modified Liquid Dilution And Agar Diffusion Methods.Jatropha curcas L. plant is widely known in Indonesian traditional medicine. The leaves and sap are often used as anti-infective drugs for sore mouth and throat. Therefore, this research aims to identify secondary metabolites contained in Jatropha leaf extract based on phytochemical screening, to determine the Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MKC) values based on the modified liquid dilution method. In addition, it also aims to determine the growth inhibition zone of Staphylococcus aureus based on the agar diffusion method. The concentration (% w / v) tested in the liquid dilution method was 0.05, 0.1, 0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75, 2 and 2.25. Furthermore, amoxicillin 30 ppm was used as positive control and 1% Na CMC as as negative control. The concentrations (% w / v) tested in the agar diffusion method were 1,1.25, 1.5, 1.75, 2 and 2.25. The phytochemical screening results of the ethanol extract showed that it contain alkaloids, flavonoids, saponins, tannins and polyphenols. The liquid dilution results showed MIC and MKC concentration of 1.25 and 1.5% w / v respectively. Moreover, the inhibition zone diameter (concentration% / mm of inhibitory power) obtained were 1 / 10.66, 1.25 / 11, 1.5 / 11, 33, 1.75 / 12, 33, 2/13 and 2.25 / 14. Based on the results, the statistically optimal concentration is determined at a concentration of 1.75% w / v.Keywords    : Jatropha leaves, Staphylococcus aureus, MIC, MKC, inhibition zoneTanaman jarak pagar (Jatropha curcas L.) telah dikenal dalam pengobatan tradisional Indonesia. Daun dan getah jarak pagar sering digunakan sebagai obat antiinfeksi seperti radang mulut dan tenggorokan.  Tujuan penelitian untuk mengidentifikasi senyawa metabolit sekunder yang terkandung dalm ekstrak daun jarak pagar berdasarkan skrining fitokimia, menentukan nilai Minimum Inhibitory Concentration (MIC) & Minimum Killing Concentration (MKC) berdasarkan metode dilusi cair termodifikasi dan menentukan zona hambat pertumbuhan Staphylococcus aureus berdasarkan metode difusi aga Konsentrasi (% b/v) yang diuji pada metode dilusi cair adalah 0,05; 0,1; 0,25;  0,5; 0,75; 1; 1,25; 1,5; 1,75; 2 dan 2,25. Kontrol positif digunakan Amoxicilin 30 ppm dan kontrol negatif yang digunakan adalah Na CMC 1%. Konsentrasi (% b/v) yang diuji pada metode   difusi   agar  adalah   1; 1,25;   1,5;   1,75;   2   dan   2,25.  Hasil skrining fitokimia Ekstrak Etanol Daun Jarak Pagar  mengandung senyawa alkaloid, flavonoid, saponin, tannin dan polifenol. Hasil pengujian dilusi cair dipeeroleh MIC dari pada konsentrasi 1,25%b/v dan nilai MKC pada konsentrasi 1,5%b/v. Hasil diameter zona hambat  (konsentrasi %/ mm daya hambat) yaitu 1/10,66; 1,25/11; 1,5/11,33; 1,75/12,33;  2/13 dan 2,25/ 14. Konsentrasi optimal berdasarkan statistika ditentukan pada konsentrasi 1,75%b/v.Kata kunci : Daun Jarak Pagar, Staphylococcus aureus, MIC, MKC, Zona hambat